Energy aspects of axisymmetric wave propagation in an infinite cylindrical shell fully submerged in liquid - Filippenko, Georgiy Viktorovich (Computational Continuum Mechanics, 2013)
The paper is devoted to modeling joint vibrations of an ideal acoustic liquid and an infinite thin empty cylindrical shell. The problem of free oscillations of the shell in the liquid space is considered in a rigorous mathematical statement. The propagating waves and energy flux in this system are analyzed. The influence of parameters of the system on vibration and acoustic fields is considered. A comparison is carried out to study the contributions of different energy transfer mechanisms in the shell and the contribution of energy propagating in the liquid to the general energy flux.